2021
DOI: 10.1172/jci140491
|View full text |Cite
|
Sign up to set email alerts
|

Sustained cellular immune dysregulation in individuals recovering from SARS-CoV-2 infection

Abstract: SARS-CoV-2 causes a wide spectrum of clinical manifestations and significant mortality. Studies investigating underlying immune characteristics are needed to understand disease pathogenesis and inform vaccine design. In this study, we examined immune cell subsets in hospitalized and non-hospitalized individuals. In hospitalized patients, many adaptive and innate immune cells were decreased in frequency compared to healthy and convalescent individuals, with the exception of B lymphocytes which increased. Our fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 56 publications
7
108
1
2
Order By: Relevance
“…A delay in pTfh response formation could be due to the T-cell dysfunction that occurs in SARS-CoV-2 infection. Many groups have described significant T-cell dysfunction in acute SARS-CoV-2 infection (4, 5, 39), and our group has recently illustrated that this dysfunction is sustained during convalescence, even in non-hospitalized individuals (6). These high magnitude pTfh responses could also be the result of persistent antigen exposure, as several groups have reported prolonged detection of SARS-CoV-2 by PCR (40, 41).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A delay in pTfh response formation could be due to the T-cell dysfunction that occurs in SARS-CoV-2 infection. Many groups have described significant T-cell dysfunction in acute SARS-CoV-2 infection (4, 5, 39), and our group has recently illustrated that this dysfunction is sustained during convalescence, even in non-hospitalized individuals (6). These high magnitude pTfh responses could also be the result of persistent antigen exposure, as several groups have reported prolonged detection of SARS-CoV-2 by PCR (40, 41).…”
Section: Discussionmentioning
confidence: 93%
“…In SARS-CoV-2 infection, initial studies reported significant lymphopenia in hospitalized patients (3). An elevation of both activation and exhaustion markers on T cells in both severe and mild disease has also been described (4)(5)(6). More recently, data on antigen-specific T-cell responses in individuals recovered from SARS-CoV-2 infection has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 is highly expressed in alveolar epithelium, heart, renal tubules and intestinal epithelial cells (7)(8)(9). Severe complications of COVID-19, such as multiple organ dysfunction syndromes (MODS) and acute respiratory distress syndrome (ARDS), might be caused by dysregulated immune response and cytokine storms (10)(11)(12). Recently, many severe cases presenting persistent fever and the involvement of two or more organ systems in children with COVID-19 have been reported, which is termed as multisystem inflammatory syndrome (MIS-C).…”
Section: Pathogenesismentioning
confidence: 99%
“…Thus, immunosenescence represents a further potential contributor to the insurgence of fatal complications in COVID-19 [ 8 , 62 , 63 ]. Lymphopenia and accumulation of immune cells showing immunophenotypic and functional signs of exhaustion were commonly documented in COVID-19 patients, correlating with age and severity [ 43 , 68 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. This strong resemblance to immunosenescence makes COVID-19 a possible scenario to deepen the knowledge about the molecular basis affecting normal immune cell metabolism/lifespan/turnover and to determine the importance of genetic variants and epigenetic modifications behind the appearance of inflammaging and immunosenescence [ 66 , 85 , 86 , 87 , 88 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%